THE EMPIRICAL RESEARCH OF THE ATTITUDE TO THE CONCEPT PATRIOTISM AND OF THE DEGREE OF ITS COMPREHENSION AMONG LATVIAN TEENAGERS UNDER CONDITIONS OF GLOBALIZATION - Marcenoka, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Succession of generations, especially under conditions of globalisation, polyculture and integration processes in circumstances of socially economic transformation of the society and state leads to the collapse of the system of traditional values and alteration of the content and meaning of numerous phenomena and concepts. The given processes in the modern society are eroding such socially moral and value landmarks as respect and love to the Motherland, self-sacrifice and patriotism, wish and ability to work for the sake of the country, aspiration to be useful for it. The Aim of the research is to determine the attitude and degree of understanding of the concept “patriotism” among Latvian teenagers. The theoretical analysis makes it possible to conclude that the main idea of the concept patriotism consists of considering it as one of the highest values of the individual and is the basis of life orientations, defining the strategy of the individual’s development, harmonisation of the society and the state. In the empirical way, the particular and the general understanding of the concept ‘patriotism’ by Latvian teenagers was defined, how patriotism is manifested, the level of pride for one’s country, ways of upbringing of patriotic values, personal qualities of a patriot / an antipatriot and the activity directed towards motivation of active actions for sake of one’s country.